2023
DOI: 10.1088/1674-4527/acdc88
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Variability Observed with Insight-HXMT in MAXI J1820+070 and MAXI J1535-571

Abstract: We present the timing analysis of the non-linear variability in two black hole low mass X-ray binaries MAXI J1820+070 and MAXI J1535-571 by using the bicoherence, a measure of phase coupling at different Fourier frequencies. We found different patterns, e.g., "cross" and "hypotenuse", for LFQPOs in different outburst states. When they can be clearly distinguished, bicoherence patterns are similar over a wide energy range of 1-100 keV. It is intriguing that in some type-C QPOs we found the patterns that norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Additionally, the bright radiation from MAXI J1820+070 indicated the presence of a perturbed accretion disk (Zhang et al 2023). For the sources MAXI J1820+070 and MAXI J1535-571, Ding et al (2023) observed cross and hypotenuse patterns, suggesting the presence of QPOs. It is plausible that these different types of QPOs could arise from similar underlying mechanisms.…”
Section: Astrophysical Motivationmentioning
confidence: 89%
“…Additionally, the bright radiation from MAXI J1820+070 indicated the presence of a perturbed accretion disk (Zhang et al 2023). For the sources MAXI J1820+070 and MAXI J1535-571, Ding et al (2023) observed cross and hypotenuse patterns, suggesting the presence of QPOs. It is plausible that these different types of QPOs could arise from similar underlying mechanisms.…”
Section: Astrophysical Motivationmentioning
confidence: 89%
“…Additionally, the bright radiation from M AXI J1820 + 070 indicated the presence of a perturbed accretion disk (Zhang et al 2023). For the sources M AXI J1820 + 070 and M AXI J1535 − 571, Ding et al (2023) observed cross and hypotenuse patterns, suggesting the presence of QPOs. It is plausible that these different types of QPOs could arise from similar underlying mechanisms.…”
Section: Astrophysical Motivationmentioning
confidence: 89%